Development of a landslide component for a sediment budget model. (June 2017) - Betts, Harley; Basher, Les; Dymond, John; Herzig, Alexander; Marden, Mike; Phillips, Chris
Abstract: Most erosion models focus on overland-flow erosion with fewer incorporating landslide erosion although it is common on hillslopes. Landslide models are typically dynamic, spatially distributed simulations with large data requirements for parameterisation and are often computationally intensive. The Australian SedNet model represents a middle ground between process-based and empirical models and is being modified for New Zealand conditions by incorporating shallow landsliding. We describe a method for implementing a model within SedNetNZ to provide the long-term annual average sediment contribution from shallow landsliding and its spatial distribution. The mass of soil eroded over a defined period is calculated from the landslide probability for each slope class, slope class area, failure depth, soil bulk density, and sediment delivery ratio. Landslide probability is derived from mapping a time series of landslides intersected with DEM-derived slope. The conceptual approach and methodology for parameterisation are suitable for landslide modelling where rainfall-triggered shallow landslides occur. Highlights: A method for modelling long-term shallow landsliding within a sediment budget model. Time series of historical landsliding mapped from aerial photography. Landslide-slope relationships derived from landslide distribution and slope. Landslide-slope relationships used to spatially model sediment generation. Applicable to any landscape subject to rain-triggered shallow landsliding.